2015
DOI: 10.1097/iae.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Network Anomalies in Branch Retinal Vein Occlusion on Optical Coherence Tomography Angiography

Abstract: In the authors’ 10 cases of branch retinal vein occlusion, OCT angiography (OCT-A) shows diffuse vascular anomalies both in the superficial and deep vascular network. Fovea avascular zone (FAZ) enlargement, capillary non-perfusion (CN-P) and microvascular abnormalities (MA) are well characterized by OCT-A in all eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 17 publications
7
73
0
2
Order By: Relevance
“…This study also suggested that the findings in the DRL were more profound than those in the SRL in RVO subjects. Several other studies have also confirmed those findings (Rispoli, Savastano et al 2015, Adhi, Filho et al 2016) and are reviewed below. Interestingly, Kashani et al also demonstrated that some regions of intraretinal fluid could be visualized on OCTA in analogy to what Matsunaga et al showed for intraretinal fluid in DR (Kashani, Lee et al 2015).…”
Section: Review Of Clinical Studies Utilizing Octasupporting
confidence: 59%
See 1 more Smart Citation
“…This study also suggested that the findings in the DRL were more profound than those in the SRL in RVO subjects. Several other studies have also confirmed those findings (Rispoli, Savastano et al 2015, Adhi, Filho et al 2016) and are reviewed below. Interestingly, Kashani et al also demonstrated that some regions of intraretinal fluid could be visualized on OCTA in analogy to what Matsunaga et al showed for intraretinal fluid in DR (Kashani, Lee et al 2015).…”
Section: Review Of Clinical Studies Utilizing Octasupporting
confidence: 59%
“…These studies have confirmed the above findings and provided novel information about the layer specific nature of impaired perfusion in RVO subjects. For example, several studies of RVO show a decrease in both superficial and deep capillary plexus density, FAZ enlargement, and microvascular abnormalities (Rispoli, Savastano et al 2015, Coscas, Glacet-Bernard et al 2016). One such OCTA study of 54 subjects with RVO (29 CRVO and 25 BRVO) attempted to characterize qualitative OCTA features, such as disruption of the perifoveolar capillary arcade, capillary abnormalities, central cysts, non-perfusion “greyish” areas, and deep capillary plexus (Coscas, Glacet-Bernard et al 2016).…”
Section: Review Of Clinical Studies Utilizing Octamentioning
confidence: 99%
“…A previous study on 10 BRVO eyes showed that OCTA was capable of detecting changes like vessel tortuosity, FAZ enlargement, CNP occurrence, etc. in BRVO eyes . Similar features were also observed in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Few qualitative and quantitative OCTA studies were published on BRVO. In OCTA images of BRVO eyes, the normalized fractal dimension ratio range of 0.0‐0.6 was chosen for computation of CNP areas.…”
Section: Discussionmentioning
confidence: 99%
“…48 Chronic changes at the border such as vascular congestion/dilation, capillary non-perfusion, vessel rarefication, telangiectatic vessels, microaneurysms, retinal neovascularization, and collaterals are visible using OCTA. [49][50][51] OCTA segmentation reveals that the deep plexus may be affected to a greater degree than the superficial plexus in retinal vein occlusions.…”
Section: Retinal Artery and Vein Occlusionsmentioning
confidence: 99%